Hard tissue nanomedicine - significance of nanostructures - Liu, Huinan (Henry Stewart Talks, 2015)
Research overview and multidisciplinary collaborations, Interface between biomaterials & cells: how biomaterials affect cell behaviors, Importance of scale, Improving hard tissue regeneration, Nanocomposites for bone regeneration, Next-generation implants, From random to ordered-surface features, Surface patterning on titanium: BMSCs as a model